Motivasi Suporter Panser Girl Dalam Mendukung Klub PSIS Semarang (Indonesian Journal for Physical Education and Sport, 2021)
Football is a popular sport in the world, even in Indonesia this sport is arguably the prima donna of Indonesian sports. Interest in this sport is not only in playing it, but by watching a soccer match can also provide a special pleasure for the community, so that not a few people like to watch soccer matches. This study aims to describe the physiological needs, safety needs, social needs, appreciation needs, and self-actualization needs for women to become supporters of the Indonesian Football Association of Indonesian Football Association (Panser Girl) Semarang.